Cuidados básicos en el hogar a las personas en tratamiento quimioterapéutico. - Paniagua Hidalgo, Diana (2012)
This article presents the results of research carried out to implement a training program on basic home care to people in chemotherapy aimed at families and caregivers in the Ana Gabriela Ross Foundation in 2010 and the appraisal. Participated in the 14 people, including relatives and caregivers. All the participants are adults, so we used the approach andragogic during the teaching process. For educational needs on the theme that developed was applied to a self-administered questionnaire validated by expert opinion. Subsequently, it was designed, developed and implemented the training program. Finally, he was evaluated by applying a pre-test and post-test. As a result there was a need relevant information effectively on the care of the person with cancer undergoing chemotherapy at home, taking into account measures for comprehensive care. There was an increase of knowledge about the home management of the person undergoing chemotherapy by the participants, who have the role of self-care agents for people in chemotherapeutic treatment when you require basic care. We conclude that home caregivers of people with cancer and are undergoing chemotherapy should be effectively trained to provide immediate basic care in a comprehensive manner and increase the coping capacity of the many experiences that are exposed.